Pengembangan BOOKLET Program Studi Bimbingan dan Konseling Sebagai Media Layanan Informasi Studi Lanjut Bagi Siswa Kelas XII Di SMK N 2 Kota Jambi - sherly Angriani; Akmal Sutja; Freddi Sarman (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2025)
This research developed a booklet as one of the information sources that can be utilized by students in selecting a study program. The aim of this study is to produce a booklet as a medium for choosing a university major in Guidance and Counseling. This research is a type of Research and Development (R&D). The research subjects were 12th-grade students at SMK N 2 Kota Jambi. Data collection in this study used questionnaires. The data analysis technique combined qualitative and quantitative data analysis. The research and development process was carried out in five stages, namely: (1) Preliminary Study, (2) Product Development, (3) Product Validation and Revision, (4) Limited Trial and Revision, and (5) Standardization and Publication. The results of this research and development showed that the feasibility of the booklet media for the Guidance and Counseling Study Program, based on validation from material experts, media experts, and guidance and counseling practitioners/teachers, falls into the good and feasible category with improvements according to suggestions. Furthermore, the response from 12th-grade students to the booklet media product for the Guidance and Counseling Study Program obtained a percentage of 85.17% from students of Class XII Accounting 3 at SMK N 2 Kota Jambi. This percentage falls into the “Good” category, and the product can be used as a medium for selecting a university major in Guidance and Counseling by 12th-grade students at senior high schools/vocational high schools/Islamic senior high schools or equivalent.